1996
DOI: 10.1007/bf01718594
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnosis of cowpea aphid-borne mosaic virus in Africa: significance for cowpea seed-indexing, breeding programs and potyvirus taxonomy

Abstract: Large-scale surveys in Africa for blackeye cowpea mosaic (B1CMV) and cowpea aphid-borne mosaic (CABMV) showed that several CABMV isolates from Southern Africa were either not or poorly recognized by monoclonal antibodies prepared to isolates collected in West Africa. Selection of three new monoclonal antibodies prepared against the Maputo (Mozambique) isolate of CABMV, and their incorporation into a revised panel of monoclonal antibodies, resulted in the assignment of four of these new CABMV isolates to existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Using monoclonal antibodies (MAbs) developed at Vancouver and host-range tests, two seed-and aphid-transmitted potyviruses, cowpea aphid-borne mosaic (CABMV), and blackeye cowpea mosaic (B1CMV), were identified as major pathogens in Africa. B1CMV isolates were separated into two serotypes (Huguenot et al 1993), and six serotypes were recognized among the CABMV isolates (Huguenot et al 1996). Other work (Huguenot et al 1994) showed that the molecular masses of the CABMV and B1CMV capsid proteins were 32 kD and 35 kD, respectively, that CABMV and related isolates reacted only with MAbs to CABMV, and that B1CMV isolates reacted only with MAbs to B1CMV.…”
Section: Molecular Biology Of Legume-infecting Viruses Lucerne Transimentioning
confidence: 97%
See 1 more Smart Citation
“…Using monoclonal antibodies (MAbs) developed at Vancouver and host-range tests, two seed-and aphid-transmitted potyviruses, cowpea aphid-borne mosaic (CABMV), and blackeye cowpea mosaic (B1CMV), were identified as major pathogens in Africa. B1CMV isolates were separated into two serotypes (Huguenot et al 1993), and six serotypes were recognized among the CABMV isolates (Huguenot et al 1996). Other work (Huguenot et al 1994) showed that the molecular masses of the CABMV and B1CMV capsid proteins were 32 kD and 35 kD, respectively, that CABMV and related isolates reacted only with MAbs to CABMV, and that B1CMV isolates reacted only with MAbs to B1CMV.…”
Section: Molecular Biology Of Legume-infecting Viruses Lucerne Transimentioning
confidence: 97%
“…These results provided additional evidence that BICMV and CABMV are different potyviruses and not strains of the same virus, as had been suggested earlier (Dijkstra et al 1987). The research led to a proposal that CABMV be recognized as a new viral species (Huguenot et al 1996). Both BICMV and CABMV were shown to be widely distributed in cowpeagrowing areas of Africa, occurring in the same field and sometimes in the same plant.…”
Section: Molecular Biology Of Legume-infecting Viruses Lucerne Transimentioning
confidence: 99%